Détection des défauts dans les systèmes photovoltaique basée sur les techniques d’intelligence artifivielle - محمد رضا, بن حوه; الساسي المختار, شريط; مروان, صنديد (Université d'El Oued, 2021)
Renewable energies are the engine of all human news activity. We consider that this energy is inexhaustible. Renewable energy systems are exposed to malfunctions and failures in their installations. These systems fail and deteriorate during the period of operation. This requires developing a diagnostic system whose main purpose is to align indicators to detect faults to preserve excellent energy production of the photovoltaic system. In-depth research is carried out to diagnose faults in the photovoltaic system using the technique of artificial intelligence, This study consists of developing a base of algorithms on the method of artificial neural networks for fault diagnosis in the photovoltaic system. الطاقات المتجددة هي محرك كل نشاط إخباري بشري. وتعتبر أن هذه الطاقة لا تنضب ، وتتعرض أنظمة الطاقة المتجددة لأعطال وفشل في منشآتها. هذه الأنظمة تفشل وتتدهور خلال فترة التشغيل. يتطلب ذلك تطوير نظام تشخيص هدفه الرئيسي هو مواءمة المؤشرات لاكتشاف الأعطال للحفاظ على إنتاج طاقة ممتاز للنظام الكهروضوئي. البحث المتعمق هو إجراء تشخيص للخطأ في النظام الكهروضوئي بفضل تقنية الذكاء الاصطناعي. تتكون هذه الدراسة من تطوير خوارزمية تعتمد على طريقة الشبكات العصبية الاصطناعية لتشخيص الأعطال في النظام الكهروضوئي.
Machine éléctrique مذكرة ماستر تخصص
Keywords: : renewable energies, solar energy, photovoltaic system; الطاقات المتجددة, الطاقة الشمسية, النظام الكهرو ضوئي